Upaya Penanggulangan Tindak Pidana Narkotika Oleh Badan Narkotika Nasional Provinsi Sumatera Selatan - Ganda Wijaya (Lex Stricta : Jurnal Ilmu Hukum, 2024)
This study examines the efforts of the South Sumatra Provincial National Narcotics Agency (BNNP Sumsel) in combating narcotics-related crimes and the factors influencing their implementation. Using an empirical juridical method with secondary data, the findings reveal that BNNP Sumsel adopts both non-penal and penal approaches. The non-penal efforts include prevention through supply control programs, demand reduction via public outreach and community empowerment, and harm reduction through rehabilitation. The penal efforts are carried out repressively through investigation, arrest, prosecution, and trial processes. Several factors affect these efforts, namely: (1) weak law enforcement due to limited personnel quality, (2) inadequate facilities and infrastructure caused by insufficient operational funding, and (3) low public participation in providing information or supporting the investigation process.